Capability of Thailand to implement newborn male circumcision: A nation-wide survey - Kriengkrai Srithanaviboonchai (2018)
This study was designed to gain baseline information on the capability of the hospitals of Thailand to provide newborn male circumcision (NC) and on the opinions of health-care personnel towards NC. Two questionnaires were sent to every hospital in Thailand that might have obstetrical services. One questionnaire requested information about the degree to which NC was provided by the hospital. The second questionnaire targeted health-care providers' opinions about NC. The response rate was 55.1% (747/1355). Of the 562 hospitals that had deliveries in 2010, 8.2% (46) provided at least one NC. Thirty-eight percent (35/92) of private hospitals and 2.3% (11/470) of government hospitals provided the service. The primary reason for performing NC was parental request (82.6%). Some providers (31.3%) said that NC was easy to perform and 39.1% thought NC was safe. Most respondents (91.8%) stated that physicians should perform the procedure instead of nurses, and choices about undergoing NC should be left to parents (55.0%). NC was rarely performed in government hospitals, and its staffs seemed to not recognize the health benefits of NC. A massive education program for health-care providers would be necessary before implementing a national program for NC. More information on the opinions of health authorities, health-care personnel and parents as well as cost-effectiveness studies are needed before a proper policy can be implemented. © 2013 2013 Taylor & Francis.